2007
DOI: 10.1016/j.ejcts.2006.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Preserved hyperaemic response in (distal) string sign left internal mammary artery grafts☆

Abstract: String sign LIMA grafts' were found in 9/52 (17.3%) patients. All patent and all 'string sign grafts' showed a shift towards a coronary flow profile in the proximal segment postoperatively. The study revealed the 'functionality' of the patent and the (distal) 'string sign LIMA graft' in regard to myocardial oxygen demand. 'String sign grafts' are 'recruitable' on demand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In addition, another patient in Group R showed the string sign in the left ITA graft. Researchers have previously demonstrated that string sign in grafts can result from graft flow competition distal to a mild stenosis [5,6]. In the patient, both MGF and PI (52 ml/min and 1.15, respectively) were within the cut-off criteria and the collateral feeding arteries disappeared in the postoperative angiography.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In addition, another patient in Group R showed the string sign in the left ITA graft. Researchers have previously demonstrated that string sign in grafts can result from graft flow competition distal to a mild stenosis [5,6]. In the patient, both MGF and PI (52 ml/min and 1.15, respectively) were within the cut-off criteria and the collateral feeding arteries disappeared in the postoperative angiography.…”
Section: Discussionmentioning
confidence: 82%
“…This study does not show any demonstrable influence of the potential graft flow competition distal to CTO in the LAD on early graft patency, although graft failure related to the competition could not be apparent until the long-term postoperative period. Graft flow competition distal to a mild stenosis is reportedly associated with graft failure [3][4][5][6]. Graft flow distal to a mild stenosis competes with antegrade native flow through the mild stenosis, whereas graft flow distal to CTO competes with retrograde native flow through collateral feeding arteries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The powerful influence of these physiologic processes has been documented in studies illustrating serial angiographic follow-up after in situ IMA grafting. Hartman et al[64] and Akasaka et al[65] both documented progression from a normal-sized in situ conduit, to a string sign several years later, and finally to a supra-normal conduit, as the native coronary circulation and non-arterial bypass grafts developed progressive disease (Figure 3). It is clear from the above discussion that this string sign is not the product of irreversible microvascular disease from vascular inflammation.…”
Section: Intraoperative Factors and Influencesmentioning
confidence: 99%
“…If the proximal stenosis in the TVECA is not functionally significant, such as described by Ding et al[58], then time-averaged WSS of the graft falls, and OSI increases, contributing to the development of a string sign configuration angiographically. This IMA conduit, under new conditions of ischemia, can physiologically respond accordingly to meet this perfusion demand deficit[64]. Over time, as the native TVECA and graft disease progressed, the IMA conduit was driven to supply more and more blood flow to that regional myocardium, resulting in significant vasodilation of the in situ conduit.…”
Section: Intraoperative Factors and Influencesmentioning
confidence: 99%